Contextualizing leadership: Transformational leadership and Management‐By‐Exception‐Active in safety‐critical contexts. Issue 3 (16th March 2017) - Willis, Sara; Clarke, Sharon; O'Connor, Elinor
Abstract : Within the existing leadership literature, the role of context for shaping the effectiveness of leadership is yet to be fully understood. One type of context that poses particular challenges for leaders is an environment where safety is highly critical (i.e., high exposure to risk and likelihood of an accident). We hypothesize that such environments call for specific transformational and transactional leadership behaviours, which differ from those behaviours most effective in less safety‐critical contexts. We tested for moderating effects of perceptions of hazard exposure and accident likelihood on the relationship between transformational leadership and Management‐By‐Exception‐Active with safety and job performance outcomes. The moderation effects of accident likelihood on the link between transformational/MBEA leadership and subordinate performance were supported, demonstrating variation in the effectiveness of leader behaviours dependent on followers' perceptions about the likelihood for an accident. MBEA leadership was found to be more strongly linked to contextual performance and safety participation if accident likelihood was high, but not under low accident likelihood conditions. Transformational leadership was found to be less strongly related to these performance outcomes in contexts where safety was perceived as highly critical. Our findings have important theoretical and practical implications, and call into question the universality of the transformational–transactional leadership framework. Practical considerations focus on the implications for managers and supervisors who operate in safety‐critical contexts. Practitioner points: Safety‐critical contexts pose particular challenges to leaders. If safety is perceived as highly critical, leaders and/or followers may hold different expectations about leadership and different leadership styles could be required compared to contexts where safety is not critical. Perceived effectiveness of transformational leadership and Management‐By‐Exception‐Active for employees' safety participation and contextual performance is influenced by employees' perceptions of the risk for an accident within their work context. Management‐By‐Exception‐Active is effective for enhancing team members' extra effort for safety and contextual performance if the perceived risk of an accident is high, but less effective if perceptions of accident likelihood are low. Managers and supervisors should therefore pay attention to employees' perceptions of risk of an accident and the factors that determine how employees perceive their context.